1999
DOI: 10.1046/j.1523-1747.1999.00803.x
|View full text |Cite
|
Sign up to set email alerts
|

Mouse Langerhans Cells Differentially Express an Activated T Cell-Attracting CC Chemokine

Abstract: Epidermal Langerhans cells represent an immature population of dendritic cells, not yet able to prime naïve T cells. Following in vitro culture Langerhans cells mature into potent immunostimulatory cells. We constructed a representative cDNA library of in vitro matured murine Langerhans cells. Applying a differential screening procedure 112 differentially expressed cDNA clones were isolated. Thirty-six clones represented cDNA fragments of the same gene, identifying it to be the most actively expressed gene ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
29
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 51 publications
0
29
1
Order By: Relevance
“…By the PCR-based differential display between "freshly isolated" immature Langerhans cells versus "cultured" mature Langerhans cells, Ross et al (66) have identified about 500 cDNA fragments whose expression was either up-or down-regulated during their maturation. By screening a cDNA library constructed from the cultured Langerhans cells with differential hybridization, they also identified that the expression of fascin, an actin-bundling protein, was markedly up-regulated during maturation (67). By searching the Human Genome Sciences nucleotide data bases with a consensus motif of C-type lectins, Bates et al (68) identified a new C-type lectin, termed DC immunoreceptor (DCIR), which was expressed by short term human DC cultures generated from CD34 ϩ progenitors as well as from CD14 ϩ monocytes.…”
Section: Discussionmentioning
confidence: 99%
“…By the PCR-based differential display between "freshly isolated" immature Langerhans cells versus "cultured" mature Langerhans cells, Ross et al (66) have identified about 500 cDNA fragments whose expression was either up-or down-regulated during their maturation. By screening a cDNA library constructed from the cultured Langerhans cells with differential hybridization, they also identified that the expression of fascin, an actin-bundling protein, was markedly up-regulated during maturation (67). By searching the Human Genome Sciences nucleotide data bases with a consensus motif of C-type lectins, Bates et al (68) identified a new C-type lectin, termed DC immunoreceptor (DCIR), which was expressed by short term human DC cultures generated from CD34 ϩ progenitors as well as from CD14 ϩ monocytes.…”
Section: Discussionmentioning
confidence: 99%
“…The major function of CCL22 appears to be the induction of chemotactic migration of activated T cells (7)(8)(9)15), predominantly of the Th2 type (16) and of CD4 ϩ CD25 ϩ regulatory T cells (17), through its specific receptor CCR4. However, another as yet unidentified receptor has also been implicated (18,19).…”
mentioning
confidence: 99%
“…However, another as yet unidentified receptor has also been implicated (18,19). The murine CCL22 is expressed by activated B lymphocytes and DC (8,9). Murine epidermal Langerhans cells (LC), an exceptionally homogeneous population of immature DC, produce CCL22 mRNA only upon maturation (9), whereas other myeloid DC transcribe CCL22 constitutively (8).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the preceeding work, we analyzed differential gene expression in maturing DC and identified several genes of functional importance, which are selectively expressed by mature DC and only very few other cell types. 7,8 For a detailed analysis, we isolated the promoter of one of these genes, encoding the actin-bundling protein fascin. This structural protein crosslinks actin filaments and was shown by us to be pivotal for dendrite formation in DC.…”
mentioning
confidence: 99%